Post-Traumatic Paradoxical Couple Therapy : Development and Effectiveness in Couples Affected by Extramarital Infidelity - Asayesh, Mohammad Hassan (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study was designed to develop a Post-Traumatic Paradoxical Couple Therapy program and to evaluate its effectiveness on mental health dimensions and post-trauma psychological maladjustments among couples Affected by Extramarital Infidelity. Methods and Materials: A single-subject design (ABA design) with two baseline phases was employed. Four participants (two couples) were selected through convenience sampling from clients at the Mental Health Centre of the Faculty of Psychology, University of Tehran, who had experienced extramarital trauma and decreased marital satisfaction. The research measures included the GHQ-28 questionnaire and a researcher-developed checklist, which were used to assess changes in couples throughout the intervention program. Quantitative data were analysed using visual graph inspection and effect size calculation. Findings: The findings indicated that the designed Post-Traumatic Paradoxical Couple Therapy model—incorporating techniques such as paradoxical scheduling symptom prescription, paradoxical timetable for reciprocity negotiation The timetable for periodical management, therapeutic communication processes, emotional catharsis facilitation, and session structuring, alongside psychoanalytic, systematic, and psychological mechanisms (e.g., elimination of negative emotions, interactive engagement, ego strengthening, and trust-building)—led to improvements in mental health, reductions in negative emotions, and enhanced relational functioning among couples affected by infidelity. Conclusion: achieving mental health and quality of life in couples who have experienced marital infidelity is a process mediated by emotional regulation, balance in relational roles, and the restoration of emotional bonds. The Post-Traumatic Paradoxical Couple Therapy program demonstrated its capacity to address one of the most complex challenges in couple therapy and may serve as a valuable model for family and couple therapists.